(untitled) - Mays, Larry W. (New York, 1996)
The book presents authoritative information about a vast range of water resources. It includes treatises on the state of the art in water resource economics and law, policy-making and planning, and system analysis and risk analysis; quality management of natural systems such as lakes, reservoirs, rivers, groundwater, estuaries, and wetlands; water supply systems, including surface and groundwater, treatment and distribution, wastewater collection and treatment, water reuse, and water demand analysis; water excess management, including floodplain hydrology and hydraulics, urban stormwater, and flood control systems; the future impact of global climate change, water resources deficit management, decision support systems; discussions of state-of the-the-art computer models for water resources
Keywords: Water supply